SINTESIS, KARAKTERISASI DAN APLIKASI BIO-IMPREGNAN DARI KULIT BATANG SAWIT - Jamaludin Malik; Adi Santoso; Jamal Balfas (Jurnal Penelitian Hasil Hutan, 2022)
The formulation of phenolic compounds extracted from biomass not only produces adhesives but can also be used as bioimpregnant. In this study, the synthesis was carried out by copolymerization of resorcinol (R) and formaldehyde (F) into the oilpalm bark extract (S) to produce SRF resin fluid. A complete characterization was carried out using FTIR, Py-GCMS, XRDand DTA. In addition, F emission was also undertaken to ensure its safety for health and the environment. The application ofbio-impregnant was done on samples of the hard (edge) and soft (middle) parts of the oil palm trunk. The results show that the oilpalm bark extract contains polyphenol components that have a strong affinity for resorcinol and formaldehyde in alkaline catalyst(NaOH 40%), so that it can form a copolymer that can be used as an impregnant. The application of the bio-impregnant canimprove the quality of the oil palm trunk in both parts from class V to class III of wood-strength classification with an increase indensity (>100%), hardness (4 times), thickness swelling in both cold and boiling water meets the requirements (<25%), as wellas formaldehyde emission that meets the standard SNI 03-2105-2006.